The Relationship Between Family Support and Eating Independence Among Children with Intellectual Disabilities - Regita Anjani; Beatrix Elizabeth; Yulta Kadang; Yulidian Nurpratiwi (Institut Kesehatan Suaka Insan, 2026)
Children with intellectual disabilities have limitations in intellectual function and adaptive behavior, influencing their daily activities, including their ability to eat independently. To improve this skill, children need support from their parents so they can practice consistently and gradually. If family support is limited, children will become dependent on others and struggle to eat on their own. This study aims to analyse the relationship between family support and independent eating in children with intellectual disabilities. Using a quantitative analytic observational study with a cross-sectional design and total sampling technique, involving 40 children with intellectual disabilities at SLB Bina Sejahtera. Data were collected using validated and reliable questionnaires and observation checklists and analyzed using the Chi-Square test. The results indicated that among the 24 respondents (60.0%) providing good family support, 20 children (74.1%) ate independently, whereas 4 children (30.8%) did not. The analysis indicates a significant relationship between family support and eating independence, with a p-value of 0.023 (< 0.05). In conclusion, family support has a significant relationship with eating independence in children with intellectual disabilities. Therefore, active and consistent family involvement through guidance and independence training is important to improve the child’s quality of life, particularly regarding daily independence, including eating activities.